Awareness, acceptability, relevance and congruence of the PNU-Negros Occidental vision, mission, and goals and objectives of the teacher education program - Fernandez, Ma. Wenna B. (Asia Pacific Higher Education Research Journal (APHERJ), 2015)
This study aimed to measure the awareness, acceptance relevance, and congruence of the Vision and Mission of Philippine Normal University and Goals and Objectives (VMGOs) of the Teacher Education Program. The descriptive-correlational method of research using a modified questionnaire was employed in this investigation. The participants of this study were the stakeholders of the University which include the faculty, administrative staff, students, alumni, cooperating school official/teacher, industry sector representative, barangay/city officials, and parents. With the use of statistical tools such as the mean, the ttest and the one-way anova, findings revealed that participants' awareness, understanding and acceptance of the VMGOs as well as relevance of the VMGOs to the needs and development of the community indicate a very great extent. Furthermore, the study showed that the educational practices and activities on the campus are to a great extent congruent to the University's mission, goals and objectives. When grouped according to the variables of gender, age, civil status, occupation and curriculum, significant differences among participants were observed in the way they perceived the relevance of the VMGOs to the needs and development of the community. Significant differences were also noted in terms of the conformity between educational practices and activities on campus and the mission, goals and objectives of the University and the Teacher Education program respectively. Based on the foregoing, it is recommended that the university must continue her present endeavor, as she intensifies effort in disseminating the VMGOs and explaining the same to the stakeholders especially the students and the members of the community. Educational practices and activities in the university must further be strengthened to fully realize the mission, goals and objectives of the teacher education program.